1996
DOI: 10.1097/00042560-199607000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of N-Linked Glycans in V4-V5 Region of Human Immunodeficiency Virus Type 1 Glycoprotein gp160 on Induction of a Virus-Neutralizing Humoral Response

Abstract: One of the functions of N-linked glycans of viral glycoproteins is protecting otherwise accessible neutralization epitopes of the viral envelope from neutralizing antibodies. The aim of the present study was to explore the possibility to obtain a more broadly neutralizing immune response by immunizing guinea pigs with gp160 depleted of three N-linked glycans in the CD4-binding domain by site-directed mutagenesis. Mutant and wild type gp160 were formulated into immunostimulating complexes and injected s.c. into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 36 publications
4
50
0
Order By: Relevance
“…In support of this theory, antibodies and CD4 ϩ T cells have been shown to recognize epitopes on the HIV env V2, V3, and V4 loops. However, the exposed loops of V1 and V5 regions of HIV env are also known to elicit antibody responses (50)(51)(52), yet neither contributed to the T h -epitope panel defined here. The question of a role, or otherwise, for antibody binding as a determinant of CD4 ϩ T cell responsiveness could be addressed experimentally by repeating the present analysis in IgϪ͞Ϫ MT mice.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this theory, antibodies and CD4 ϩ T cells have been shown to recognize epitopes on the HIV env V2, V3, and V4 loops. However, the exposed loops of V1 and V5 regions of HIV env are also known to elicit antibody responses (50)(51)(52), yet neither contributed to the T h -epitope panel defined here. The question of a role, or otherwise, for antibody binding as a determinant of CD4 ϩ T cell responsiveness could be addressed experimentally by repeating the present analysis in IgϪ͞Ϫ MT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, with simian immunodeficiency virus it has been shown that de-glycosylation events within the V1 region of the envelope result in a virus with increased antibody neutralization potential (61). With HIV-1, the N-linked glycosylation pattern has also been shown to have a varied effect on the induction of neutralizing antibodies (44,(62)(63)(64)(65)(66)(67). It is therefore possible that the selection of viruses with different coreceptor utilization patterns and replication phenotypes, based upon altered envelope glycosylation events, may be aided by the escape from a neutralizing antibody response.…”
Section: Figmentioning
confidence: 99%
“…These include guinea pig [127,128], turkey [129,130], cat [47,58], rabbit [39,41,43,131], dog [132], seal [133], sheep [134][135][136], pig [137], cow [138,139], and horse [140,141]. Of particular interest with regard to human applications is the ability of ISCOMs to induce strong immune responses in monkeys.…”
Section: Applications Of Iscomsmentioning
confidence: 99%